Integrating ecological research into wildlife conservation planning (Zoological Records and Reviews, 2025)
The translation of ecological research into effective wildlife conservation planning remains one of the central challengesof applied conservation science, with a well-documented gap between the production of ecological knowledge and itsuptake in management decisions. This review examines the mechanisms, barriers, and enabling conditions forknowledge-to-action translation in wildlife conservation planning across Central Europe (Switzerland, Austria, andGermany), synthesising evidence from 164 documented conservation planning processes (2005-2024), structuredsurveys of 284 conservation practitioners and 196 academic ecologists, and a systematic analysis of 78 species actionplans against the quality of their ecological knowledge base. Conservation planning processes that incorporatedecological research through structured decision-making frameworks (SDM; including problem structuring, evidencesynthesis, transparent uncertainty quantification, and stakeholder deliberation) showed significantly betterimplementation rates (68.4% vs. 34.8% of planned actions implemented within 5 years; OR = 3.94, 95% CI: 2.28-6.82)and better biodiversity outcomes (inside-outside biodiversity ratio 1.48 +- 0.18 vs. 1.12 +- 0.14) than those using informalknowledge integration. Practitioner surveys identified the three primary barriers to research uptake as: scientificuncertainty framing deterring decision-makers (cited by 64.8%); temporal mismatch between research timescales andpolicy cycles (58.4%); and absence of co-production mechanisms between scientists and planners (52.4%). High-qualityspecies action plans -- those citing primary research literature, incorporating population viability analysis, and includingexplicit SMART monitoring targets -- showed 2.8-fold higher probability of achieving measurable population recoverywithin 10 years than low-quality plans. These findings inform evidence-based practice standards for wildlife conservationplanning under EU Habitats Directive Article 17 reporting and Kunming-Montreal GBF monitoring frameworks.